A coordinated effort: Cultural and policy requirements for digital accessibility. Issue 2 (10th November 2021) - Clark, Jasmine
Abstract: Ensuring access to library technology for disabled users and staff is essential for libraries. However, recent surveys reveal that many are still struggling to develop the infrastructure required to accomplish this. The author's own research in making a digital scholarship space and its technology inclusive of disabled patrons will act as a case study and be the basis for a five-step framework for implementing accessibility workflows and practices. The results of recent surveys, an overview of disability legislation, a dialogue around challenges with vendors, and other logistical factors related to supporting accessible technology, will also be discussed.